Sistem Pendukung Keputusan Kelayakan Pemberian Asuransi Jiwa Untuk Nelayan dengan Menggunakan Metode Vikor (Studi Kasus: Dinas Kelautan dan Perikanan Medan) - Amatillah Nasution; Kurnia Ulfa (STMIK Budi Darma, 2020)
Life insurance is a term used to refer to actions, systems, or businesses in which financial protection (or financial compensation) for life, property, health and so on gets reimbursed from unexpected events that can occur such as death , loss, damage or illness, which involves regular premium payments over a period of time in exchange for a policy that guarantees such protection. The term